A survey of information literacy credit courses in US academic libraries: Prevalence and characteristics. Issue 4 (14th November 2016) - Cohen, Nadine; Holdsworth, Liz; Prechtel, John M.; Newby, Jill; Mery, Yvonne; Pfander, Jeanne; Eagleson, Laurie
Abstract : Purpose: There is a lack of data about information literacy (IL) credit courses in US academic libraries. This paper aims to provide a detailed snapshot of IL credit courses, including percentages of libraries that offer credit courses, the number of credits offered, the audience and how public institutions differ from private nonprofits and for-profits. Design/methodology/approach: The authors surveyed a stratified random sample of libraries at higher education institutions across all categories from the Carnegie Classification of Institutions of Higher Education. Qualtrics software was used to create and distribute the email survey. The response rate was 39 per cent ( n = 691). Findings: In all, 19 per cent of the institutions in the survey have IL credit courses taught by librarians. Large institutions, public institutions and those granting doctoral degrees are the most likely to offer IL credit courses. The majority of these courses are undergraduate electives of 1-2 credit hours offered under the library aegis, although a significant minority are required, worth 3-4 credit hours, and taught within another academic department or campus-wide program. Originality/value: The findings update previous surveys and provide a more granular picture of the characteristics of librarian-taught credit-bearing courses, the types of academic institutions that offer them and compensation teaching librarians receive. This survey is the first study of credit-bearing IL instruction to include for-profit colleges and universities.